Manufacturing Process of Cutting Edge of Shredder Plastic Machine Using Material Mild Steel - Hendra, Hendra; Oktavanni, Syahda Dwi; Rosyadi, Imron; Haryadi, Haryadi; Yusuf, Yusvardi; Ula, Shofiatul; Nugraha, Kurnia; Lusiana, Rina; Hernadewita, Hernadewita (Universitas Sultan Ageng Tirtayasa, 2024)
Plastic waste is a type of waste that is difficult for the soil to decompose and of course its volume increases all the time, however we still need plastic in our daily lives for various needs, for this we need tools that are able to recycle plastic so that it can be reused and become more valuable material. In recycling plastic waste, plastic shredding machines are used to chop plastic waste with various types of cutting edges, various manufacturing methods and various types of chopped products that are formed later. The aim of this research is to recreate or manufacture plastic chopping cutting edges by testing PET plastic chopping with different masses, by manufacturing using a hand grinder as the cutting tool. On a PET type plastic cup with a mass of 20 grams, it took 215 seconds to produce a chop with the smallest dimensions, namely 1mm – 6.35mm. With the cutting blade that has been made, it can chop PET type plastic with the smallest dimensions possible.